EKSTRAK DOPAMIN TANAMAN KECUBUNG (Datura metel L.) SEBAGAI AGEN ANTISTRES TERNAK DOMBA LOKAL DALAM PROSES PENANGANAN PRAPENYEMBELIHAN - Julian Gesang Palasmorojati (Journal of Livestock Science and Production, 2024)
Pre-slaughter livestock handling during Eid-ul-Adha that often does not pay attention to animal welfare causes livestock stress. Repeated stress conditions can reduce meat quality due to depletion of glycogen and lactic acid supplies and decreased meat pH. This study was conducted to determine the effect of using dopamine from amethyst leaf extract (Datura metel Lin) to reduce stress and control behaviour during pre-slaughter of ruminants. This research method uses a completely randomised design (CRD) method conducted on four local sheep aged 7-8 months with a body weight range of 20-25 kg. The provision of complete feed branded Japfa Comfeed Gemuk I with different doses of amethyst extract including P0 = 0 x 10-2 mg, P1 = 2,5 x 10-2 mg, P2 = 3,5 x 10-2  mg, P3 = 4,5 x 10-2 mg. Livestock treated with P3 had a significant effect (P 0.5) on the provision of dopamine which was characterised by livestock being calmer, not bleating, leaning down earlobes and not stomping in the cage than livestock treated with P0, P1, and P2.